Pojok Baca Sebagai Media Literasi dan Sosialisasi Gemar Menabung Sebagai Pendidikan Finansial Pada Siswa Sekolah Dasar - Annisa Rahmawan; Sulistia; Jojor Putriyani Sirait; Muhammad Fahmi Wiratma; Intan Pratiwi; Mimi rosadi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract This community service activity is part of the Regular Community Service Program (KKN) carried out in Sei Suka Deras Village, Sei Suka Subdistrict, Batu Bara Regency. The focus of this activity is to highlight the importance of literacy and the utilization of the Reading Corner as an enjoyable literacy medium that sparks interest among elementary school students. It also includes a campaign to promote a saving habit as part of financial education for students at SD Negeri 06 Sei Suka Deras. By providing engaging and age-appropriate reading materials, students are introduced to basic financial concepts such as the importance of saving from an early age, managing pocket money wisely, and distinguishing between needs and wants. The activities were conducted through an educational and participatory approach to foster reading habits and financial awareness from an early age. The results of this program show that the Reading Corner successfully increased students' interest in reading and served as an effective medium for delivering financial messages in a simple and enjoyable manner. Thus, the Reading Corner has the potential to become an educational tool for financial literacy that is easy to understand and implement in an elementary school environment. Keywords: Reading Corner, Literacy, Saving, Financial Education